(untitled) (Iraqi Journal of Civil Engineering, 2008)
The geometric design of highway alignment consists mainly of the design of horizontal alignment and Vertical alignment. The more important step in horizontal alignment design is the curve radius determination. The equation used for horizontal curve radius determination is developed with assumption that when vehicle run on curved section, there are an acting force on it. This force include the centrifugal force that try to push vehicle out off its path , on the other hand there are resisting forces try to keep the vehicle on its path. Those include the friction between road surface and tires and forces resulting from sloping the highway cross section. When a vehicle on rural highway with high embankment the wind Pressure will play an important role in force system acting on vehicle because of increasing in wind pressure intensity at these conditions (rural highway, i.e open areas, high embankment). The purpose of this paper is to present a new equation for horizontal curve radius determination taking in to account the wind force effect in addition to other forces acting on vehicle The resulting equation relates vehicle length, height and weight and the wind pressure as well as the other factors in traditional equation. Effect of each parameter on design radius was investigated for the case where the wind direction is acted with the same centrifugal force direction. It has been found that the required minimum radius increase with the decreasing of vehicle weight or in the other words the vehicle permitted speed decrease with the decreasing of vehicle weight. On the other hand, the required curve radius increases with vehicle height increasing. Consequently, permitted height of bags loaded on a truck is related to the type of loads. Derived equation can also be used for estimation of the permitted truck speed on existing roads especially in case of bad weathers The comparison between the traditional and suggested equation showed that maximum difference is about 160 % which results at high wind pressure while the difference is up to 20 % for low wind pressure